Technical and Financial Aspects of White Shrimp (Litopenaeus vannamei) Culture in Coastal Sandy Soil Area of Bantul Regency - Triyatmo, Bambang; Suadi, Suadi; Ambarwati, Dian; Sukardi, Sukardi (Aquacultura Indonesiana, 2016)
This research has been conducted to know the technical and financial aspects of white shrimp (Litopenaeus vannamei) culture in Bantul District coastal sandy soil area. The samples of farmers were determined by stratified sampling method based on the ponds width. The data were colected by observation and interviews methods. The samples in the study were 41 farmers as respondents/ponds from the population of 290 ponds. Samples were consisted of three categories : 1,000 m2 per pond for 16 farmers: 1,000-1,500 m2 per ponds for 14 farmers and >1,500 – 2,500 m2 per pond for 11 farmers. The results showed that the white shrimp culture in Bantul District coastal sandy soil area was an intensive system with average pond width 1,300 m2. Average pond category < 1,000 m2 was 636 m2; average pond category 1,000-1,500 m2 was 1,357 m2 and average pond category >1,500 – 2,500 m2 was 2.191 m2. Generally the fixed costs incurred IDR 24,876,128,- per pond/cycle and variable costs IDR 72,839,121 per pond/cycle (IDR 218,517,362,- per pond/year). The revenue of the culture was IDR 109,709,805,- per pond/year, with the ratio value  between the total revenue with total costs [Revenue (R) / Cost (C) ratio ] was 1.37. The Break Event Point  (BEP) of shrimp products was 4,909 kg and the Break Event Point (BEP) of shrimp price was IDR 34,312,-. The highest productivity of shrimp was 19.7 Ton/ha/cycle, which be cultured in the 1,000-1,500 m2 ponds, with incomed IDR 169,507,143 per pond/cycle and the Revenue/Cost ratio (R/C ratio) was 1.60.  The BEP of shrimp products was 5,069 Kg and the BEP of shrimp price was IDR 28,187,-